2022
DOI: 10.1007/s00383-022-05133-y
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric surgical trials, their fragility index, and why to avoid using it to evaluate results

Abstract: Background The fragility index has been gaining ground in the evaluation of comparative clinical studies. Many scientists evaluated trials in their fields and deemed them to be fragile, although there is no consensus on the definition of fragility. We aimed to calculate the fragility index and its permutations for paediatric surgical trials. Methods We searched pubmed for prospectively conducted paediatric surgical trials with intervention and control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 65 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…In general, studies in other surgical fields have also revealed low FI values [11]. Thus, in head and neck surgery [12] with 27 RCTs the FI was 1 (0–2.5), in urology [13] with 41 trials it was 3 (1.4–5), and in paediatric surgery [14] and ophthalmology [15] with 156 attempts it was 2 (0–48).…”
Section: Discussionmentioning
confidence: 99%
“…In general, studies in other surgical fields have also revealed low FI values [11]. Thus, in head and neck surgery [12] with 27 RCTs the FI was 1 (0–2.5), in urology [13] with 41 trials it was 3 (1.4–5), and in paediatric surgery [14] and ophthalmology [15] with 156 attempts it was 2 (0–48).…”
Section: Discussionmentioning
confidence: 99%